Cetirizine suppression to skin prick test results in atopic allergy patients - Soegiarto, Gatot; Kurnia, David; Effendi, Chairul; Konthen, Putu Gedhe (Folia Medica Indonesiana, 2017)
This study was done to determine the suppression index of Cetirizine to the skin prick test results to obtain a correction constant or factor that can be used to assess the results of the skin prick test in patients who cannot stop the use of antihistamines (Cetirizine). This pre and post test study design clinical trial involved 22 atopic allergy patients who seek medical treatment at the Allergy and Immunology Outpatient Clinic Dr. Soetomo Hospital. Skin prick tests were done twice (SPT1 and SPT2) using house dust mite allergen extract to all study subjecs. The first (SPT1) were done after washout of all antihistamine for 1 week prior the test. All study subjects were then given Cetirizine 10 mg once daily for 5 days and on day 6 we performed the second test (SPT2). Cetirizine suppresion index and correction factor were calculated by comparing the wheal area of SPT1 and SPT2. All 22 study subjects (6 males and 16 females) were sensitized to house dust mite allergen. Mean serum total IgE levels were 176.42 + 352.5 IU/dL. Mean wheal area generated by the positive control (histamine 1 mg/mL) in SPT1 was 7.53 + 7.31 mm2, and in SPT2 was 1.08 + 1.46 mm2. Mean wheal area generated by house dust mite allergen in SPT1 was 43.57 + 36 mm2, and in SPT2 was 10.28 + 8.47 mm2. Cetirizine suppression index for positive controls (histamine 10 mg/mL) was 94.63 + 7.90% (p=0.000), while the Cetirizine suppression index for house dust mite allergen is 72.31 + 13.96% (p=0.000). There was no significant influence of serum total IgE levels to Cetirizine suppression index (p=0.381). The correction constant based on the calculation was 1.9. In conclusion, Cetirizine suppression index to the mean wheals area generated by house dust mite allergen was 72.31% and the correction constant was 1.9. In allergic patients who cannot stop their antihistamine drugs, Cetirizine 10 mg once daily can be used as a replacement and they still be able to undergo skin prick tests. The actual wheal diameter (or area) of the skin prick test results can be calculated by multiplying the measured wheal diameter (or area) under the Cetirizine administration with the correction constant.